Assessment of Antibiotic Prescription in Respiratory Tract Infection at Hera General Hospital in Makkah Almukarramah, KSA - B., Rafea; F., Alharbi; G., Alhazmi; L., Alahmadi; M., Almotiri; M., Alharthi; M., Alsulami; R., Alamri; R., Alkhallaf; R., Hettah; Y., Alhindi (International Journal of Innovative Research in Medical Science, 2019)
Introduction: In general practice, approximately two-thirds of antibiotic prescriptions are for respiratory tract infections. Acute respiratory tract infections, which include acute uncomplicated bronchitis, pharyngitis, rhinosinusitis and the common cold, are often common reasons for acute outpatient visits to physicians and antibiotic prescriptions for adults. The improper treatment of acute respiratory tract infections is now an urgent public health threat, as it is an important contributor to antibiotic resistance. In developing countries, including Saudi Arabia, antibiotics are prescribed excessively and are often obtained without prescription. Aim: The aim of this study was to gather information on current antibiotic prescribing rates for respiratory tract infection in Hera General Hospital Makkah Almukarramah, Saudi Arabia. Method: A cross-sectional study, incorporating systematic sampling on clinical data from antibiotic prescriptions in hospitalised and emergency departments at Hera General Hospital, was conducted. From September 2017 to April 2018, approximately 500 prescriptions were collected from each hospitalised and emergency pharmacy for patients with respiratory tract infections. Results: The most prescribed antibiotics for respiratory tract infections came from the penicillin group and ciprofloxacin. The prescribing of antibiotics for respiratory tract infections was more prevalent amongst males than females. Potential over-prescribing of antibiotics for upper respiratory tract infections specially patients with otitis media especially in children without proper lab investigations.